Evolution of symbiosis in the legume genus Aeschynomene - Chaintreuil, Clémence; Arrighi, Jean-François; Giraud, Eric; Miché, Lucie; Moulin, Lionel; Dreyfus, Bernard; Munive-Hernández, José-Antonio; Villegas-Hernandez, María Del Carmen; Béna, Gilles (The New phytologist, 2013)
Legumes in the genus Aeschynomene form nitrogen-fixing root nodules in association with Bradyrhizobium strains. Several aquatic and subaquatic species have the additional capacity to form stem nodules, and some of them can symbiotically interact with specific strains that do not produce the common Nod factors synthesized by all other rhizobia. The question of the emergence and evolution of these nodulation characters has been the subject of recent debate. We conducted a molecular phylogenetic analysis of 38 different Aeschynomene species. The phylogeny was reconstructed with both the chloroplast DNA trnL intron and the nuclear ribosomal DNA ITS/5.8S region. We also tested 28 Aeschynomene species for their capacity to form root and stem nodules by inoculating different rhizobial strains, including nodABC-containing strains (ORS285, USDA110) and a nodABC-lacking strain (ORS278). Maximum likelihood analyses resolved four distinct phylogenetic groups of Aeschynomene. We found that stem nodulation may have evolved several times in the genus, and that all Aeschynomene species using a Nod-independent symbiotic process clustered in the same clade. The phylogenetic approach suggested that Nod-independent nodulation has evolved once in this genus, and should be considered as a derived character, and this result is discussed with regard to previous experimental studies.